Composição química e produção forrageira de três variedades de capim-elefante - Marques Vieira , Luiz; Alberto Gomide, José (Revista Ceres, 2025)
This experiment was conducted at Universidade Rural do Estado de Minas Gerais, Vigosa, in a loamy, acid and low fertility soil. The purposewas to study the influence of frequency of cutting upon the yield and chemical composition of three varieties of elephantgrass (Pennisetum purpureum Schum.).